Near-unity absorption in a graphene-embedded defective photonic crystals array. (April 2017) - Bian, Li-an; Liu, Peiguo; Han, Zhenzhong; Li, Gaosheng; Mao, Jian; Lu, Zhonghao
Abstract: Near-unity absorption is achieved theoretically at the terahertz frequencies by the graphene-based absorber under the condition of approaching critical coupling. The designed structure is composed of a defective photonic crystal array equal to the multilayer subwavelength grating, which possesses simultaneously the properties of photonic crystal and subwavelength grating so that both FP resonance and Fano resonance are excited. To simulate the structure accurately, rigorous coupled-wave analysis is employed. It is found that the dip can be introduced into the high absorption spectrum by the coupling of two resonances, which is realized by tuning the chemical potential of graphene, the geometry and equivalent thickness of grating as well as the angle of incident wave. The unusual absorption spectra are believed to be useful in the detection and modulation of terahertz waves. Highlights: Near-unity absorption is achieved under the condition of approaching critical coupling. Both FP resonance and Fano resonance are excited simultaneously. The coupling of two resonances is realized by multiple tuning modes. The coupled absorption spectra can be used in the detection and modulation of terahertz waves.